One-year spatiotemporal variations of air pollutants in a major chemical-industry park in the Yangtze River Delta, China by 30 miniature air quality monitoring stations - Pang, Xiaobing; Lu, Yu; Wang, Baozhen; Wu, Hai; Shi, Kangli; Li, Jingjing; Xing, Bo; Chen, Lang; Wu, Zhentao; Dai, Shang; Zhou, Wei; Cui, Xuewei; et al. (Frontiers in Environmental Science, 2022)
Fine chemical industrial park (FCIP) is a major source of atmospheric pollutants in China. A long-term high spatial resolution monitoring campaign on air pollutants had been firstly conducted in a major FCIP in Yangtze River Delta (YRD) from December 2019 to November 2020. The grid-based monitoring platform consisting of 30 miniature air quality monitoring stations (AQMSs) provided comprehensive coverage of a FCIP, and long-term monitoring studies solved the problem of lack of clarity about pollution sources in industrial parks. Overall, NO2 pollution was particularly high in the pharmaceutical industry, while TVOCs and O3 pollution were most serious in the textile dyeing industry, with PM pollution much higher in the metal smelting industry than in other industries, and in the leather industry, O3 pollution was relatively severe. The spatial and temporal variations of air pollutants showed that higher PM, CO and NO2 concentrations were revealed in winter while lower in summer due to better meteorological diffusion conditions. TVOCs concentrations were higher with an average of 1954 ppb in summer possibly due to their increased volatilization from their sources at higher ambient temperatures. O3 concentrations were at their peaks in spring (88.8 μg m−3) and early fall (78.5 μg m−3). The daily trends of O3 precursors (TVOCs and NO2) were clearly negatively correlated with O3, and they showed bimodal peaks due to anthropogenic activities, plant emissions, lowering of the mixed boundary layer, etc. The O3 formed in FCIP was judged to be NO2-limited during the monitoring period based on the ratios of NO2 to TVOCs. Therefore, the effective strategy to reduce O3 formation in FCIP is to decrease the ambient NO2 concentration. Based on Pearson correlation coefficients, it appeared that WS promoted O3 formation through long-term transport and that high air temperatures also contributed to O3 formation in the environment. It was also stated in the study that the closer the residential area is to the industrial sources, the more significant the correlation. Thus, the results of this study will also be helpful for policymakers to design pollutant control strategies for different industries to mitigate the impact of pollutants on human health.